Design and Development of a Web-Based Student Discipline Evaluation Information System Using a Research and Development Approach - Hendra Parsaulian; Donny Maulana; Annisa Maulana (Journal of Information System Research (JOSH), 2026)
Student discipline management is an essential component of educational administration that supports the creation of a conducive learning environment. However, disciplinary management at SMA Negeri 2 Cikarang Selatan was previously conducted manually using notebooks and spreadsheet applications, resulting in data redundancy, inaccurate calculation of violation points, delays in report generation, and difficulties in monitoring students' disciplinary records. This study aims to design and develop a Web-Based Student Discipline Evaluation Information System to improve the efficiency, accuracy, and transparency of disciplinary management. The study employed the Research and Development (R&D) approach, which consisted of needs analysis, system design, system development, implementation, and system evaluation. The proposed application was developed using PHP and MySQL and integrated several functional modules, including user authentication, student data management, violation recording, automatic point calculation, report generation, and user management. Functional evaluation was conducted using the Black-Box Testing method to verify that each module operated according to the specified requirements. The evaluation results indicated that all functional modules performed successfully without significant errors, demonstrating that the developed system satisfied the identified functional requirements. Compared with the previous manual procedure, the proposed system improved administrative efficiency, enhanced data accuracy through automated point calculation, facilitated faster report generation, and increased accessibility to disciplinary information through a centralized web-based platform. The developed system also strengthened communication among administrators, teachers, guidance counselors, and student guardians by providing accurate and timely disciplinary information. Therefore, the proposed Web-Based Student Discipline Evaluation Information System can serve as an effective digital solution for modernizing student discipline management and supporting evidence-based decision-making in educational institutions.